The longitudinal associations between mental health indicators and digital media use and physical activity during adolescence: A latent class approach. (March 2022) - Engberg, Elina; Hietajärvi, Lauri; Maksniemi, Erika; Lahti, Jari; Lonka, Kirsti; Salmela-Aro, Katariina; Viljakainen, Heli
Abstract: Introduction: Evidence for the relationship between movement behaviors and mental health among adolescents is inconclusive. We aimed to identify profiles of digital media use (including related bedtime delay) and leisure-time physical activity (LTPA) in adolescence, and to examine whether preadolescent mental health predicted later behavior profiles. Methods: This study included 1285 participants assessed at 11 years of age, and followed-up four years later. Participants completed the Self-Perception Profile for Children (SPPC), Center for Epidemiological Studies Depression Scale for Children (CES-DC) and Screen for Child Anxiety-Related Emotional Disorders (SCARED) at baseline, and reported digital media use (active and passive use, gaming, and related bedtime delays) and LTPA at follow-up. A latent class approach was employed to identify behavior profiles, membership of which was then predicted with mental health and covariates, including baseline digital media use and LTPA. Results: We identified four behavior profiles: 1) high digital media use/moderate LTPA (20% of adolescents; 78% boys), 2) moderate digital media use/high LTPA (31%; 28%), 3) high digital media use/high LTPA (26%; 15%), 4) high passive digital media use and gaming/low LTPA (23%; 89%). After adjusting for covariates, higher LTPA and better perception of athletic competence at baseline associated with higher odds of belonging to any other profile than to the unhealthiest profile (4) at follow-up. Symptoms of depression or anxiety did not associate with later behavior profiles. Conclusions: LTPA and related self-esteem seem to be stronger predictors of future digital media use and LTPA behavior during adolescence than mental health symptoms alone. Highlights: We conducted a 4-year follow-up study in adolescents. We assessed mental health indicators at 11 years of age. We assessed physical activity and different types of digital media use at 15 years of age. We identified four behavior profiles of digital media use and physical activity. Physical activity and related self-esteem were the strongest predictors for later behavior profiles.